2021
DOI: 10.3390/cancers13143422
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of CD206 in Solid Malignancies: A Systematic Review and Meta-Analysis

Abstract: An increased presence of CD206-expressing tumor associated macrophages in solid cancers was proposed to be associated with worse outcomes in multiple types of malignancies, but contradictory results are published. We performed a reproducible systematic review and meta-analysis to provide increased evidence to confirm or reject this hypothesis following the Preferred Reporting Items for Systematic Reviews and Meta-analyses statement. The Embase, Web of Science, and MEDLINE-databases were systematically searched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 66 publications
1
11
0
Order By: Relevance
“…For example, clusters of macrophages that actively express the macrophage mannose receptor (MMR) and have a proangiogenic effect are found in hypoxic regions of tumors. Data reported by Debacker et al [ 79 ] confirm these conclusions. They analyzed 27 clinical cases and found that patients with high levels of MMR expression in tumor microenvironment macrophages exhibited a significantly lower survival rate than patients without overexpression of this biomarker.…”
Section: Tumor Microenvironment Biomarkers In the Diagnosis Classific...supporting
confidence: 63%
“…For example, clusters of macrophages that actively express the macrophage mannose receptor (MMR) and have a proangiogenic effect are found in hypoxic regions of tumors. Data reported by Debacker et al [ 79 ] confirm these conclusions. They analyzed 27 clinical cases and found that patients with high levels of MMR expression in tumor microenvironment macrophages exhibited a significantly lower survival rate than patients without overexpression of this biomarker.…”
Section: Tumor Microenvironment Biomarkers In the Diagnosis Classific...supporting
confidence: 63%
“…CD206 is a membrane-bound protein consisting of distinct extracellular structural domains, a transmembrane fragment and a cytoplasmic tail, and is normally expressed on macrophages and dendritic cells ( 49 ). CD206 can recognize and bind to a variety of ligands such as peptide hormones, lysosomal hydrolases and mannose and their derivatives, and is regulated by these ligands to initiate its clearance process ( 50 ).…”
Section: Strategies To Reeducate Tamsmentioning
confidence: 99%
“…Given that the phenotype of macrophages is often characterized by differences in the expression of various surface receptors, and CD206 macrophage mannose receptor is usually overexpressed on M2 polarized macrophages and TAMs, it is allowed to construct mannose modified nanocarrier to target M2 and TAMs. [ 36 , 37 ] In this study, we further explored and prepared mannose‐functionalized porous silicon nanoparticles (Man@pSiNPs), a functional nanocarrier that can specifically target TAMs. Figure 7 A depicts the schematic illustration of the Man@pSiNP preparation.…”
Section: Resultsmentioning
confidence: 99%